IMMANENT CHARACTERISTICS OF CREATIVITY IN A KNOWLEDGE SOCIETY - Tkachenko, Lidiia (Continuing Professional Education: Theory and Practice, 2019)
The article deals with peculiarities of creative acts of the individual in modern terms. The knowledge society (or post-modern society) imposes the following requirements for the individual that contribute to its daily work. Now you want to talk about binding not only creative expressions in all spheres of life, but also new attribute, that there is its internal characteristics of creativity immanent characteristics. They should consider the regularity and the transience of changes, the prevalence of intellectual work of the modern period of social development and so on. The creative work of the modern personality should be marked not only by the novelty, but also by a number of features for satisfying the modern society’ circumstances. First, it is inherently present innovation. The creative act should be organically integrated into the overall flow of the progress. Creativity in any field should include high intellectual product that is distributed both on the cognitive, so non-cognitive level. These features are the key to such characteristic as flexibility that is now perhaps the most desirable feature of innovation. All these intentions must be present in the man’s work and creation. Creativity is observed not as a separate act of life – it should be everyday attitude to life situations, motivated by the readiness to solve the problems, an integrated person’s ability to identify and implement his/her own capabilities. The challenges of the society and respond to them are not only a necessity that one should satisfy with the help of creative efforts. It is also a way of updating of the creative potential of the individual, and therefore – one’s own personal growth.